VF arrest secondary to immune checkpoint inhibitor (ICI)-associated myocarditis; improving patient outcomes by maintaining a high clinical suspicion for ICI toxicity - Victoria Floyd-Ellis (Clinical Medicine)
Introduction: Use of immune checkpoint inhibitor (ICI) medications has revolutionised clinical outcomes and remains an exciting prospect in oncology as further indications are revealed.1 However, adverse effects, or toxicities, secondary to their non-targeted immunological activation create an array of complications that require prompt recognition and management not only by oncologists, but also all clinicians.2This case highlights the often subtle, non-specific presentation of ICI toxicities that reveal significant pathological processes and consequences for patients. Improving patient outcomes by maintaining a high clinical suspicion for ICI toxicity, which can be confounded by pre-existing medical conditions, is demonstrated here in a case of ventricular fibrillation (VF) arrest revealing ICI-myocarditis. Case presentation: A 74-year-old woman presented with nausea and fatigue 12 days following her second cycle of adjuvant pembrolizumab for stage 2 malignant melanoma. Her past history included hypertrophic cardiomyopathy. On arrival, she appeared well. She was afebrile and haemodynamically stable, with a regular heart rate of 94 bpm with no pedal oedema or breathlessness. A mild immunotherapy toxicity was felt to be responsible for her presentation and discharge was considered, but disregarded in favour of further monitoring. A few hours later,the patient was found in cardiac arrest; cardiopulmonary resuscitation (CPR) including two DC-cardioversion shocks for VF were required to achieve return of spontaneous circulation.VF arrest secondary to ICI-myocarditis with underlying hypertrophic cardiomyopathy was subsequently diagnosed. In view of a 600% troponin rise (baseline 29 ng/L to 170 ng/L), fatigue and ventricular arrhythmia, a fulminant ICI myocarditis was favoured, in accordance with the European Society of Cardio-Oncology (ESCO) definition.3Treatment included admission to the intensive care unit (ICU), starting immunosuppression (corticosteroids and mycophenolate) and a dual chamber ICD implant 12 days post-arrest. The patient made a good recovery and returned to all pre-admission activities. Discussion: Of all ICI toxicities, myocarditis is a rare complication, but carries a mortality rate as high as 50%.4 Its presentation varies widely, with only two other cases presenting with cardiac arrest being described in the literature.5,6 A systematic review reported presenting cardiac symptoms in only 47.1% of 238 ICI myocarditis cases. 12.6% reported non-specific symptoms, while 10.1% were asymptomatic. 30.3% presented with neuromuscular symptoms, a reminder that ICI myocarditis often develops as ‘triple-M syndrome’, concurrent with myositis and/or myasthenia gravis.7The systematic review echoes the importance of maintaining a low threshold for suspecting and investigating ICI myocarditis despite ambiguous symptoms.ESCO recognises that cancer therapy-related cardiovascular toxicity (CTR-CVT) risk is varied and provides suggestions for the level of attention such patients require depending upon the combination of likelihood (based on reported incidence) and degree (severity or grade) of adverse events. It also aids with CVT risk stratification pre-treatment, considering patients’ baseline cardiac risk factors and cancer therapy.3According to ESCO, the underlying cardiac history and ICI timeline stratify this reported patient in the most vulnerable group for cardiac toxicity. The decision to monitor the patient was lifesaving, reinforcing that maintaining a low threshold to investigate causes of vague, non-specific symptoms in patients receiving ICI treatment can significantly improve patient outcomes, particularly those with predisposing risk factors.